Attacking foreign assets - Campbell, Dennis; Center for International Legal Studies (London ; New York : Lloyd's of London Press, 1992)
The book seeks to set out the basic parameters which govern the strategies and remedies available to the foreign creditors in 27 jurisdictions
"Published in association with the Center for International Legal Studies."
Includes bibliographical references and index.
gp 22/01/2019
Loans
Keywords: Conflict of laws; Obligations (Law); Alien property